Democracy model based on Bali local wisdom values for capacity building of regional governance - Suacana, I Wayan Gede; Suaib, Eka (International research journal of management, IT and social sciences, 2016)
This research was conducted applying a qualitative method for assessing governance in Bali Region. The stage of research began with the collection of primary and secondary data. The second stage was choosing a theory as a means of analyzing the data. The third stage analyzed and interpreted the data that had been selected. The fourth stage was to do the writing and construction of research results. The results showed that the values of the local wisdom of Bali, which is reflected in its democratic models, showed how the government and people of Bali held a governance rule. Strengthening institutional capacity and the capacity of the policy was strongly supported by the development of this democratic model. In this context, there is a symmetrical relationship between the accountability and transparency of government who is regarded as Guru Wisesa with the level of public trust in him.